Monthly variation in the qualitative and qualitative Composition of zooplankton (Copepoda , Cladocera) In Diyala river and and two of its branches - Al – Doori, M. L . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The seasonal variation of two groups of Zooplankton were studied in Diyala river and two branches , about 30Km from Diyala dam It was found that there are differences in the distribution of the two groups . Atotal of six species were identified of Copepoda in Diyala river and its two branches . The species are Cyclops vernalis . C . visinus , C . dimorphus , Mesocyclops laukartu ,Paracyclops affinis and Diaptomus reighardi , where recorded high annual density in Khalis stream . Its annual density was between 0.55 – 20.66 Ind . / L. Wheras, Cladocera group 14 species were identified . and the most disturbance species were Bosmina longirostris , B . corigoni , Moina micrura , Alonella excise , Leptodra kiniditii . However , the annual density was ranged between 1.68 – 29.38 Ind . / L, and the highest annual density for Bosmina longirostris was 29.38 Ind . / L . in Diyala river b